TAFSIR ALQURAN TENTANG AKAL (Sebuah Tinjauan Tematis) - Zein, Arifin (Department of Alquran Science and Interpretation of the Faculty of Ushuluddin, Adab, and Dawah of IAIN Langsa, 2017)
This article discusses reason in the concept of the Koran. Aql in the Quran repeats as many as 49 times, except for one, all come in the form of fiil mudhari, especially the material that continues with wawu jamaah. Like the form of taqilun or yaqilun. The verb taqilun is repeated 24 times and the verb yaqilun is 22 times. Whereas, the verbs aqala, naqilu, and yaqilu each have one time. From a number of verses of the Quran it can be understood that, reason has several meanings, including the power to understand and describe something, moral drive and power to take lessons and conclusions and wisdom